1968
DOI: 10.1001/archpedi.1968.02100020533014
|View full text |Cite
|
Sign up to set email alerts
|

Effective Use of Comprehensive Pediatric Care

Abstract: THE POOR are demanding that America consider and deal with their problems, social, economic, and medical. America, as a nation, is demanding that the medical profession provide high quality, yet compassionate medical care for all its citizens.While the doctor-patient relationship always has been considered the sine qua non of medical practice, a double standard has developed for low-income families.The care of this group of patients is described as episodic, fragmented, crisis oriented, and anonymous.1 The abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1971
1971
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…21,37,45,57,58 In 7 of the studies, including 6 of the 7 clinical trials, patients were assigned either to a clinic designed to deliver clinician continuity or to a clinic with no physician continuity. [22][23][24][25][26]29,40,70 Unfortunately, the quality of evidence in these studies is compromised, because in only 1 study was continuity actually measured in either study group. 33 Supplemental Table 3 (http://www.annfammed.org/ cgi/content/full/3/2/159/DC1) summarizes the 20 studies examining the association between interpersonal continuity and the cost of health care.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…21,37,45,57,58 In 7 of the studies, including 6 of the 7 clinical trials, patients were assigned either to a clinic designed to deliver clinician continuity or to a clinic with no physician continuity. [22][23][24][25][26]29,40,70 Unfortunately, the quality of evidence in these studies is compromised, because in only 1 study was continuity actually measured in either study group. 33 Supplemental Table 3 (http://www.annfammed.org/ cgi/content/full/3/2/159/DC1) summarizes the 20 studies examining the association between interpersonal continuity and the cost of health care.…”
Section: Resultsmentioning
confidence: 99%
“…One of the cohort studies examined interpersonal continuity as the dependent variable in a managed care environment and found a signifi cant association between more restrictive utilization and increased continuity of care. References 21,22,24,26,32,38,40,43,45,49,50, 56. † References 22,24,26,29,[43][44][45][46]50,52,55, 60.…”
mentioning
confidence: 99%
“…A mid-1960s experiment that offered primary care to a group of poor families found that free comprehensive services increased physician use and reduced hospitalizations, and an evaluation of a Medicaid managed care program in Maryland found that the number of primary care visits was inversely associated with avoidable hospitalizations. 14,25 Neither of these studies examined specifically the concept of adherence to guidelines for pediatric care.…”
Section: Discussionmentioning
confidence: 99%
“…One of the best known examples is a study of the introduction of &dquo;comprehensive family-focused pediatric&dquo; care at the children § Hospital Medical Center in Boston in the mid-1960s (Alpert et al 1968;Alpert et al 1970;Heagarty et al 1970). The initial article (Alpert et al 1968) noted, &dquo;The absence of a single physician to provide both preventive and curative services precludes the development of any relationship between doctor and patient.&dquo; The studies reported improvements in performance-more well visits, less sick visits, less hospitalization, more patient satisfaction, and better patient knowledge about when to use. The reason given for the reduced hospital use was: &dquo;It seems likely that physicians with a stable relationship with their patients are more comfortable in treating illnesses on an outpatient basis when the indication for hospitalization is not certain.…”
Section: Effect Of Managing Physicianmentioning
confidence: 99%
“…The reason given for the reduced hospital use was: &dquo;It seems likely that physicians with a stable relationship with their patients are more comfortable in treating illnesses on an outpatient basis when the indication for hospitalization is not certain. Their knowledge of the family adds to their control of the situation&dquo; (Alpert et al 1968). This conclusion seems reasonable; note its similarity to the Breslau and Haug statement presented earlier.…”
Section: Effect Of Managing Physicianmentioning
confidence: 99%